ESTIMATION OF OCCUPATIONAL ACCIDENTS IN TURKEY UNTIL 2030 (Natural Resources and Technology, 2023)
Today, as a result of the development of technology, the prodution power of companies and the increase in the competition between themselves have led to the emergence of dangers especially for occupational safety. The 21st century, in which industrialization and production techniques have come to the fore, has been a period in which deaths and disabilities have increased as a result of work accidents caused by machines. In this study, the number of occcupational accidents in Turkey until 2030 was estimated by using artificial neural network on the Weka package program. While creating the model, the numbers of  compulsory insured workers, workplace, work accident, death as a result of work accident and permanent incapacity for work were used between 1970 and 2021. %30 of the data was used as test data and %70 as training data in the neural network. In the light of the result, the expected number of occupational accidents in 2030 is estimated as 642210.
Keywords: Artificial Neural Networks; Occupational Accident; Time Series; Turkey